2021
DOI: 10.1080/09638237.2021.1875413
|View full text |Cite
|
Sign up to set email alerts
|

Mental health, quality of life, wellbeing, loneliness and use of social media in a time of social distancing during the COVID-19 outbreak. A cross-country comparative study

Abstract: Background: The COVID-19 outbreak raised questions about how people experience their mental health, quality of life (QoL), wellbeing and loneliness in the context of social distancing, and the use of social media during this time Aims: To examine the experience of mental health, QoL, wellbeing and loneliness and use of social media among people living in Norway, USA, UK and Australia. Methods: A crosscountry comparative survey of people living in Norway, USA, UK and Australia. Relevant statistical analyses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
128
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 162 publications
(158 citation statements)
references
References 41 publications
12
128
0
Order By: Relevance
“…This qualitative study was part of a wider trans-national on-line survey about mental health, wellbeing, loneliness and the use of social media during the pandemic (Geirdal et al 2021). The cross-sectional survey was made available between April and May 2020.…”
Section: Methodsmentioning
confidence: 99%
“…This qualitative study was part of a wider trans-national on-line survey about mental health, wellbeing, loneliness and the use of social media during the pandemic (Geirdal et al 2021). The cross-sectional survey was made available between April and May 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to many other nations, contagion was mild. In this early phase, a recent study has also demonstrated that population levels of mental distress were also less severe [77]. The recruitment of patients referred to specialized treatment may limit the generalizability of the situation for PD patients across nations, contexts, and availability of PD health services.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The study is a sub-study of a larger cross-national comparative survey concerned with the impact of social distancing on mental health and quality of life during the early stages of the COVID-19 outbreak [20,21]. Recruitment to the study was performed by distributing the link to the web-based survey via social media; thus, participants in the study were likely to be regular social media users.…”
Section: Study Limitationsmentioning
confidence: 99%